2014
DOI: 10.1128/aac.03021-14
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Selection of Escherichia coli Sequence Type 131 in a Mouse Intestinal Colonization Model

Abstract: The ability of different antibiotics to select for extended-spectrum ␤-lactamase (ESBL)-producing Escherichia coli remains a topic of discussion. In a mouse intestinal colonization model, we evaluated the selective abilities of nine common antimicrobials (cefotaxime, cefuroxime, dicloxacillin, clindamycin, penicillin, ampicillin, meropenem, ciprofloxacin, and amdinocillin) against a CTX-M-15-producing E. coli sequence type 131 (ST131) isolate with a fluoroquinolone resistance phenotype. Mice (8 per group) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…To the extent that traits regarded conventionally as associated with extraintestinal VGs also promote gut colonization (27), the abundance and distinctive combinations of VGs present in ST131 may confer enhanced fitness in the intestinal niche, thereby potentially contributing to ST131's epidemiological success (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that traits regarded conventionally as associated with extraintestinal VGs also promote gut colonization (27), the abundance and distinctive combinations of VGs present in ST131 may confer enhanced fitness in the intestinal niche, thereby potentially contributing to ST131's epidemiological success (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the impact of cephalosporins on microflora. In a mouse intestinal colonization model, cefotaxime, given subcutaneously once a day for 3 days, has no impact on Bacteroides or aerobic Gram-positive flora evaluated using culture methods (29).…”
Section: Discussionmentioning
confidence: 99%
“…The association between tetracycline use and ESBL resistance, as previously described for other antibiotics, may be mediated by transferable multidrug resistance plasmids [27]. The association between lincosamide use and ESBL resistance is supported by case-control and experimental studies [14,15,28]. Incidentally, clindamycin has also been reported to promote carbapenemase-producing K. pneumoniae carriage in a murine model, and its use has been associated with vancomycin resistance in Enterococcus spp.…”
Section: Discussionmentioning
confidence: 81%
“…However, these results have to be confirmed. Considering the number of antibacterial agents that may promote ESBL resistance, a systematic analysis of the link between ESBL resistance and consumption of most antibiotics used in the hospital is necessary [15]. Our objective was to explore the association between ESBL incidence and hospital use of various classes of antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%